The Renminbi on the internationalisation trail - Sylvain Plasschaert (European Centre for International Political Economy (ECIPE), 2012)
The rise of the renminbi (RMB) as a key currency in international financial markets has been fast. It reflects China's general expansion in the "real" world economy, and its accumulation of official foreign exchange reserves. There is no doubt that the role of the RMB for the global economy will increase. Just three decades ago, that seemed like a very remote notion. The question now is if the RMB will assume a pivotal role as an instrument for transactions in international trade and investment as well as, ultimately, as a reserve currency. First, however, one should clarify what is actually meant by "internationalisation" of a currency. This paper analyses the various distinct areas in which that process unfolds. The internationalisation of the RMB has a distinct Chinese flavour in the sense that the symbiotic role of (the Special Administrative Region of) Hong Kong requires special attention. The next important step towards internationalisation appears to be an extension of RMB convertibility to encompass purely financial transactions. Ultimately, the issue whether and when the RMB might reach the coronation stage as a major reserve currency is linked to broader questions about reconstructions of the international monetary system, primarily the dominating role of the U.S. dollar. Although the RMB appears slated for such a prominent role given China's increasing weight in the world economy, this paper will argue that such an event is not likely to take place soon but in the distant future.
Keywords: F02; F33; 330; China; Renminbi; international monetary system; capital account liberalisation